Usages numériques domestiques et réussite scolaire. Le rôle de la socialisation familiale - Agnès Grimault-Leprince; Lila Le Trividic Harrache; Laurent Mell
Digital technologies are playing an increasingly important role in schools - a situation that has been further accentuated by the COVID-19 pandemic - with the aim of renewing the school institution and reducing social inequalities in academic achievement. While schools' strategy is essentially based on uses in the school envi-ronment, the digital uses of students go far beyond this framework. This article proposes a reflection on family socialization to digital uses and its links with school success. Based on a quantitative survey of 822 families (teenagers in 7th grade and their parents), it shows that teenagers' informational research related to school culture is unequally profitable academically and strongly differentiated according to the social back-ground. The research also emphasizes the uncertain nature of the family transmission of digital skills and dispositions favorable to academic success.